Penggunaan ETAP 12.6 Sebagai Alat Bantu Dalam Memilih Setting OCR Untuk Melindungi Kelangsungan dan Kestabilan Energi Listrik - Hidayat, Renaldi; Kartadinata, V. Budi; Olivia Sereati, Catherine; Octavianus Bachri, Karel (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2022)
In this time electrical energy is one of the most energy used. In industry electrical energy becomes a necessity that cannot be separated from the production process. Due to the need for electrical energy sources, of course, a protection system is needed to maintain the continuity and stability of electrical energy from existing disturbances such as short circuit disturbances. To overcome the short circuit, OCR is used. To assist the process of calculating loadflow and short-circuit current, ETAP12.6 is used. The results of the analysis of the ETAP 12.6 will be compared with the data obtained in the field with the aim of analyzing whether the use of the ETAP 12.6 software in assisting calculations and analysis in the selection of OCR settings. The difference in ocr settings in the ETAP 12.6 and field data has a difference of less than 2%. This difference is relatively small and can still be used to help the process in selecting the OCR settings.